2015
DOI: 10.1074/jbc.m114.630053
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan Inhibits Insulin Signaling through GRB10-mediated Decrease in Tyr(P)-IRS1 and through Inflammation-induced Increase in Ser(P)307-IRS1

Abstract: Background:The common food additive carrageenan inhibits insulin signaling by increasing Ser(P) 307 -IRS1, leading to reduced Ser(P) 473 -AKT. Results: Carrageenan also inhibits insulin signaling by increasing expression of GRB10, an inhibitor of Tyr(P)-IRS1. Conclusion: Combined effects of carrageenan on Tyr(P)-IRS1 and Ser(P) 307 -IRS1 completely block the insulin-induced increase in Ser(P) 473 -AKT. Significance: Carrageenan impairs glucose tolerance by inflammatory and transcriptional effects that lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 44 publications
(39 reference statements)
2
22
0
1
Order By: Relevance
“…It has been confirmed that an imbalance of insulin signaling pathway is one of the principal cause of insulin resistance, e. g. the IRS1/AKT signaling pathway. Phosphorylation of IRS1 Ser307 accounts for insulin resistance, whereas insulin sensitivity is promoted with elevated hepatic AKT activity [39,40]. In our study, knockdown of leap2 in HFD-fed mice attenuated glucose tolerance and insulin sensitivity, while the insulin-related IRS1/AKT signaling was activated.…”
Section: Discussionsupporting
confidence: 48%
“…It has been confirmed that an imbalance of insulin signaling pathway is one of the principal cause of insulin resistance, e. g. the IRS1/AKT signaling pathway. Phosphorylation of IRS1 Ser307 accounts for insulin resistance, whereas insulin sensitivity is promoted with elevated hepatic AKT activity [39,40]. In our study, knockdown of leap2 in HFD-fed mice attenuated glucose tolerance and insulin sensitivity, while the insulin-related IRS1/AKT signaling was activated.…”
Section: Discussionsupporting
confidence: 48%
“…Based on findings in previous mechanistic studies, additional outcome measures of interest were the inflammatory measures: serum IL-8, cellular phospho-(Ser307)-IRS1, and phospho-(Ser473)-AKT1. These had been shown to be modified in previous studies of carrageenan exposure [13][14][15].…”
Section: Methodsmentioning
confidence: 87%
“…Oral carrageenan caused systemic inflammation, leading to impaired insulin signaling in the mouse liver. Carrageenan exposure inhibited insulin signaling by effects on both hepatic phospho-insulin receptor substrate 1 (IRS1) and growth-factor receptor bound protein 10 (GRB10) [13][14][15]. Carrageenan increased phospho-(Ser307/312)-IRS1, a negative regulator of insulin signaling, and reduced phospho-Tyr-IRS1, a positive regulator of insulin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as a negative mediators of insulin signaling, ser (P) 307 -IRS−1 blocks the interaction between the IRS−1 and IR, which may lead to the insulin resistance [27]. On the contrary, insulin-initiated the increase in tyrosine phosphorylation of IRS−1 exhibited a positive effects on insulin sensitivity in C57BL/6J mice [28]. In our previous study, the level of ser (P) 307 -IRS−1 was increased in the hippocampus of diabetic rats with depression [15].…”
Section: Discussionmentioning
confidence: 99%